FRI0574 RENAL TISSUE EPIGENETIC BIOMARKERS' CHARACTERIZATION IN PATIENTS WITH LUPUS NEPHRITIS AS PARAMETERS OF DISEASE ACTIVITY, REMISSION AND FLARE. (13th June 2020) - DI Mario, C.; Petricca, L.; Vischini, G.; Paglionico, A.; Alivernini, S.; Costanzi, S.; Gigante, M. R.; Bui, L.; Varriano, V.; Federico, F.; Tanti, G.; Grandaliano, G.; et al.
Abstract : Background: Epigenetic factors such as non-coding RNA (miRNA) have been shown to be deregulated in Systemic Lupus Erythematosus (SLE). In particular, in mouse model (1), different miRNAs have been associated with lupus nephritis (LN), one of the most severe manifestations of the disease. Objectives: The aim of the study was to evaluate the expression of miR-155 and miR-34a in renal tissue as biomarkers of organ involvement and inflammatory tissue activity in patients with LN. Methods: Thirty-two LN patients with active renal involvement were enrolled (age: 32.2 ± 9.2 years). The nephritic onset of the disease (early-SLE) was present in 13 patients (41%), while 19 patients (59%) showed a renal involvement during the follow-up (long-SLE). Clinical, laboratory and demographic data were collected for each patient. Disease activity was recorded using SLEDAI-2K and renal activity, using the total SLEDAI-2K fraction including the items related to the renal involvement. Ultrasound-guided renal biopsy has been performed for each patients for the definition of the nephritic class according to the ISN / RPS classification of 2003 revised in 2018(2). The expression of miR-155 and miR-34a in renal tissue was carried out by extraction of total RNA from paraffin-preserved biopsies and after a retrotrascription protocol was evaluated using SYBR® Green-based real-time PCR by relative quantification considering the ΔCt (Ct miRNA- Ct housekeeping gene)(3). Results: Mir-155 and miR-34a expression in renal tissue were comparable in the different histological classes. Dividing patients on the base of nephritic onset, patients with early SLE showed lower expression of miR-155 (ΔCt 12.8 ± 10.8) and miR-34a (ΔCt 14.6 ± 9.9) than patients with long-SLE (miR-155: ΔCt 6.1 ± 8.7 p = 0.02; miR-34a: ΔCt 7.1 ± 9.0 p = 0.03). Furthermore, a direct correlation was observed between the expression of miR-155 and miR-34a (r = 0.91, p <0.001). Considering patients with early-SLE, the expression of miR-34a was slightly significant in patients who had relapsed (ΔCt 8.2 ± 11.4 vs ΔCt 18.4 ± 7.9 p = 0.08), although no correlation emerged between the expression of miR-155 and miR-34a both at the time of the biopsy and with the disease activity indices. At the histological evaluation, miR-155 and miR-34a were more expressed in Early-SLE patients who had wire loop lesions (miR-155: ΔCt 19.5 ± 7.7 vs ΔCt 7.3 ± 9.6 p = 0.05; miR-34a: ΔCt 21, 7 ± 1.1 vs ΔCt 8, 8 ± 9.7 p= 0.05) possibly associated with a greater activation of the inflammatory component. Conclusion: MiR-155 and miR-34a may represent tissue biomarkers of inflammatory activation in patients with LN in particular the higher expression of these miRNA in Long-SLE patients could indicate a possible role of these biomarkers in renal involvement in patients with SLE with later renal onset. The increased expression of miR-34a could give indications of a disease recurrence suggesting a closer monitoring of the patient. References: [1] Leiss H et al. Plosone 2017 [2] Bajema IM et al Kidney Int. 2018 [3] Alivernini S et al. Nat Commun 2018 Disclosure of Interests: None declared